IMPLEMENTASI METODE PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Dini Apriliani Khairunissa Gurnadi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the application of the Problem Based Learning (PBL) model in PAI learning to improve students' critical thinking skills. PBL is a learning approach that involves students in solving real problems, which can train their analytical and critical skills. The research used a qualitative approach with a literature review method, analyzing journals, books, and documents related to the application of PBL in PAI. The results of the analysis show that PBL can improve the quality of PAI learning by giving students direct experience in solving problems relevant to real life, as well as encouraging the development of social and moral skills. However, challenges such as longer time and changes in the roles of teachers and students in the learning process need to be overcome so that the implementation of PBL can be optimized. This study recommends proper problem planning, the role of the teacher as a facilitator, and the integration of moral values in learning to increase the effectiveness of PBL in PAI.